Influence of dietary n-3 long-chain fatty acids on microbial diversity and composition of sows’ feces, colostrum, milk, and suckling piglets’ feces - Llauradó-Calero, Eudald; Climent, Eric; Chenoll, Empar; Ballester, Maria; Badiola, Ignacio; Lizardo, Rosil; Torrallardona, David; Esteve-Garcia, Enric; Tous, Núria (Frontiers in Microbiology, 2022)
Very little is known about the impact of n-3 long chain fatty acids (n-3 LCFA) on the microbiota of sows and their piglets. The aim of this study was to evaluate the effect of n-3 LCFA in sow diets on the microbiota composition of sows’ feces, colostrum, and milk as well as that of piglets’ feces. Twenty-two sows were randomly assigned to either a control or an n-3 LCFA diet from service to weaning. Sows’ and piglets’ performance was monitored. The gestating and lactating sows’ microbiome in feces, colostrum, and milk were characterized by 16s ribosomal RNA gene sequencing. The fecal microbiome from the two lowest (>800 g) and the two highest birth weight piglets per litter was also characterized, and the LPS levels in plasma analyzed at weaning. n-3 LCFA increased microbiota alpha diversity in suckling piglets’ and gestating sows’ feces. However, no effects were observed in colostrum, milk or lactating sows’ feces. Dietary n-3 LCFA modified the microbiota composition of gestating sows’ feces, milk, and suckling piglets’ feces, without affecting lactating sows’ feces or colostrum. In gestating sows’ feces and milk, the decrease in genus Succinivibrio and the increase of Proteobacteria phylum, due to the increased genera Brenneria and Escherichia, respectively stand out. In feces of suckling piglets, the higher abundance of beneficial genus Akkermansia and Bacteroides, and different species of Lactobacillus is highlighted. In addition, positive correlations for families and genera were found between lactating sows’ feces and milk, milk and suckling piglets’ feces, and lactating sows’ feces and suckling piglets’ feces. To conclude, dietary n-3 LCFA had a positive impact on the microbiome of suckling piglet’s feces, by increasing microbial diversity and some beneficial bacteria populations, had a few minor modifications on the microbiome of milk and gestating sows’ feces, and did not change the microbiome in lactating sows’ feces or colostrum. Therefore, this study shows the effect of dietary n-3 LCFA on the microbiota of sows, colostrum, milk and suckling piglets during the lactation period providing crucial information of the microbiota status at the early stages of life, which have an impact on the post-weaning.